Optimization of a Shared-Aperture Dual-Band Transmitting/Receiving Array Antenna for Radar Applications - Kwon, Gina; JoonYoung Park; DongHwan Kim; Keum Cheol Hwang (IEEE transactions on antennas and propagation, 2017)
In this paper, a design algorithm for a sharedaperture dual-band transmitting/receiving array antenna is proposed for active array radar applications. Sand X-band elements are located on a single planar aperture, but the transmitting and receiving apertures are separated for simultaneous transmitting and receiving. First, difference sets and a genetic algorithm (GA) are used to optimize the transmitting thinned arrays with radiation characteristics equivalent to those of a periodic array. For the receiving thinned array, a GA is applied to derive the array configurations and quadratic programming is utilized to calculate the feed signals. To verify the design algorithm, 17 × 7 transmitting arrays and 17 × 17 receiving arrays are designed, manufactured, and measured by utilizing a dipole antenna and Vivaldi antenna as the Sand X-band elements, respectively. Moreover, mutual coupling between the array elements is considered when computing the radiation pattern in an effort to ensure accurate predictions of the radiation characteristics. The measured peak sidelobe levels (PSLs) without beam scanning for the Sand X-band transmitting arrays are -12.12 and -12.4 dB, and the half-power beamwidths (HPBWs) are 5.38° × 14.65° and 5.44° × 12.75°, respectively. For the receiving array, low PSLs of -23.2 and -22.35 dB are obtained at 3.1 and 9.5 GHz, while the measured HPBWs are 7.45° × 7.01° and 7.95° × 8.11°. No grating lobes occur for either the transmitting or receiving array antenna within the target scan angle range.